Performance of irrigated bean cultivars in the Cerrado-Amazonian ecotone - Soares, Matheus Bortolanza; Lima, Joaquim Pedro de; Freddi, Ona da Silva; Tavanti, Tauan Rimoldi [UNESP]; Rimoldi Tavanti, Renan Francisco [UNESP]; Wruck, Flavio Jesus (Univ Federal Mato Grosso, 2019)
The use of central pivot irrigation favors third-crop bean cultivation, however, productivity limitations are observed when cultivated in a no-tillage system, with surface compaction, nematode incidence and vertical and horizontal spatial variability of soil nutrients, main limiting factors of this system. The objective of this study was evaluate the performance of third-crop irrigated bean cultivars grown under no-tillage system and the correlation with soil fertility and nematode incidence in the Cerrado-Amazonian ecotone region. The experiment was developed in the Sorriso-MT county in a Dystrophic Red Yellow Latosol. The treatments consisted of four bean cultivars: BRS Estilo, BRS Notavel, BRS Ametista and BRS Perola, in a total area of 9900 m(2), where soil chemical and plant attributes were determined through 83 georeferenced sampling points. The statistical procedures used were: descriptive analysis of the data, geostatistical analysis and comparison of means by the bootstrap method. Most of the attributes presented moderate to high spatial dependence, with high spatial variability. The increase of potassium contents generated increases in productivity, while the increase in the incidence of nematodes, potential acidity and aluminum saturation in the soil resulted in a reduction. The highest productivity observed was of the cultivar BRS Perola, indicating good aptitude for cultivation in this region.
Keywords: Phaseolus vulgaris L.; soil fertility; nematode; geoestatistics